Penerapan Pembelajaran PAI Berbasis Video Learning Bagi Peserta Didik Disabilitas Tunarungu Di SMPLB Negeri Tamanwinangun - Muna, Kunti Nailal; Murtajib, Ahmad (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This research aim to know the design and application of video learning in Islamic Religious Education (PAI) learning, to analyze the response of deaf students to video learning-based PAI, and to identify supporting and inhibiting factors for its implementation at SMPLB Negeri Tamanwinangun Kebumen. This study uses a descriptive qualitative approach. The research site is at SMPLB Negeri Tamanwinangun Kebumen. The research subjects included PAI maple teachers and deaf students in grade IX B. The data collection techniques used were observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing to conclusions. The results of the study show that the application of video learning is specifically designed as a solution to verbal communication barriers in deaf students. Video design must include Indonesian Sign Language (BISINDO), text/subtitles, and interesting visualizations so that the material is easy to understand. The response of deaf students to this media was positive, shown by increased learning motivation and understanding of PAI concepts. The main supporting factors are the activeness and creativity of students and school support, while obstacles include limited facilities and infrastructure and difficulty finding video teaching materials that are in accordance with the material and needs of learners.